Distinguishing subtypes of endothelial cells in the mouse aorta - Liqun He; Riikka Pietilä; Yuyang Miao; Elisa Vazquez-Liebanas; Marie Jeansson; Loren G. Fong; Stephen G. Young; Maarja Andaloussi Mäe; Lars Muhl; Christer Betsholtz (Proceedings of the National Academy of Sciences, 2025)
This study reanalyzed endothelial cell (EC) gene expression in the mouse aorta utilizing eight single-cell RNA-sequencing datasets. Contrary to the assumption that all ECs originated from the luminal surface, we identified two distinct sites of origin: aortic lumen ( Cytl1 -positive ECs) and peri-aortic microvascular ( Gpihbp1 -positive ECs). The proportions of these EC subtypes varied extensively across the eight datasets, likely due to differing experimental procedures. We deduced complete transcriptomes for each EC subtype, revealing differential gene expression and predicted functional properties. We provide marker lists and an accessible online database for gene-by-gene analysis to aid in correct cell identification and in gauging the impact of patho/physiological parameters on aortic EC gene expression.